Diversity and phylogenetic community structure across elevation during climate change in a family of hyperdiverse neotropical beetles (Staphylinidae). Issue 5 (29th January 2021) - Dolson, Sarah J.; Loewen, Elyssa; Jones, Kelsey; Jacobs, Shoshanah R.; Solis, Angel; Hallwachs, Winnie; Brunke, Adam J.; Janzen, Daniel H.; Smith, M. Alex
Abstract : Environmental stress from abiotic conditions imposes physiological limits on individuals within communities, and these stressful conditions can act as a filter on the species present in any given environment. Such abiotic stressors can reduce a community's diversity and make its composition more phylogenetically clustered. Using a decade of staphylinid beetle (Staphylinidae, Coleoptera, rove beetles) collections made across a 1500 m elevation gradient in northwestern Costa Rica (2008–2017) we asked what species lived there, how large and overlapping were the communities across this gradient, and what relationship was there between elevation and diversity. Using DNA barcodes for identification and phylogenetic estimates of community structure, we found high turnover across elevation, and that staphylinid diversity increased linearly with elevation. Because of this, we found staphylinid diversity was negatively related to surface area and temperature, and positively with precipitation. We suggest that historical biogeography and contemporary environmental stress have combined to produce these observed patterns. The forests in which these beetles are found are heating and drying rapidly and our finding that diversity increases with elevation suggests that there will be catastrophic biodiversity loss in the coming decades.